Pengaruh Pengendalian Internal Dan Moralitas Individu Terhadap Kecenderungan Kecurangan Akuntansi Pada Perusahaan Dagang Di Kota Padang - Mayang Dewinda Putri; Gerry Hamdani Putra (Jurnal Kendali Akuntansi, 2023)
The tendency of accounting fraud has attracted a lot of media attention and has become an issue that is often heard and important in the eyes of world business people. Not only in the BUMN sector but also in companies engaged in Merchandising. The city of Padang which is the capital of the province of West Sumatra which also has many companies engaged in Merchandising. The purpose of this study was to determine how the effect of the effectiveness of internal control and individual morality on the tendency of accounting fraud in merchandising companies in the city of Padang. This type of research is quantitative research. The population used in this study were all employees who carry out accounting duties and functions in merchandising companies in the city of Padang. Data were collected by distributing questionnaires directly to the respondents concerned. The data analysis technique used is multiple linear regression with the help of SPSS 22. The results showed that the effectiveness of internal control had no effect on the tendency of accounting fraud in merchandising companies in the city of Padang, while the individual morality had a negative effect on the tendency of accounting fraud in merchandising companies in the city of Padang.